Financial Literacy and Financial Education Theory and Survey - Swiecka, Beata (De Gruyter Oldenbourg, 2019)
It is a well-known saying that money does not buy happiness. But it certainly helps in life. It is important to have enough of it to satisfy our needs and to secure ourselves from emergency situations. That's what adults think. And what about the youth? What is their approach to money, what do they know about finances and how are their skills in everyday financial management coming along? What kind of knowledge and skills should be provided? Do young people in different countries represent similar or different approaches to financial matters? Using the results of a research on young people in Poland and Germany, the authors draw a picture of financial literacy. They furthermore present a number of recommendations that help developing the knowledge and the financial skills of young people in practice.